Pakcoy's (Brassica rapa L.) Response to the Provision of Liquid Organic Fertilizer in Polybags - Budiyati Ichwan; Irianto Irianto; Eliyanti Eliyanti; Mapegau Mapegau; Zulkarnain Zulkarnain; Ikhbal Ikhbal (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2023)
This study aimed to examine the effect of Liquid Organic Fertilizer (LOF) in increasing the growth and yield of pakcoy, as well as obtaining LOF concentrations that provided the best growth and yields of pakcoy plants. It was conducted at the Teaching and Research Farm, Faculty of Agriculture, University of Jambi, 35 asl. The study used a Randomized Block Design with one factor, namely various LOF concentrations: 0ml/l; 5ml/l; 10ml/l, 15ml/l. Each treatment was repeated five times. The results showed that LOF application was able to increase the growth and yield of pakcoy plants in the form of plant height (4.94%–24.49%), number of leaves (4.63%–9.26%), leaf area (18.17%–46.12%), dry weight (50.98%–94.90%), and plant fresh weight (50.46%–102.60%). The LOF concentration of 10ml/l provided the best pakcoy growth and yield. The results of this study have just been able to produce a fresh weight of pakcoy 26%–33% of the potential pakcoy yield.